Different Array CGH profiles within hereditary breast cancer tumors associated to BRCA1 expression and overall survival. Issue 1 (December 2016) - Alvarez, Carolina; Aravena, Andrés; Tapia, Teresa; Rozenblum, Ester; Solís, Luisa; Corvalán, Alejandro; Camus, Mauricio; Alvarez, Manuel; Munroe, David; Maass, Alejandro; Carvallo, Pilar
Abstract Background Array CGH analysis of breast tumors has contributed to the identification of different genomic profiles in these tumors. Loss of DNA repair by BRCA1 functional deficiency in breast cancer has been proposed as a relevant contribution to breast cancer progression for tumors with no germline mutation. Identifying the genomic alterations taking place in BRCA1 not expressing tumors will lead us to a better understanding of the cellular functions affected in this heterogeneous disease. Moreover, specific genomic alterations may contribute to the identification of potential therapeutic targets and offer a more personalized treatment to breast cancer patients. Methods Forty seven tumors from hereditary breast cancer cases, previously analyzed for BRCA1 expression, and screened for germlineBRCA1 and2 mutations, were analyzed by Array based Comparative Genomic Hybridization (aCGH) using Agilent 4x44K arrays. Overall survival was established for tumors in different clusters using Log-rank (Mantel-Cox) Test. Gene lists obtained from aCGH analysis were analyzed for Gene Ontology enrichment using GOrilla and DAVID tools. Results Genomic profiling of the tumors showed specific alterations associated toBRCA1 or2 mutation status, and BRCA1 expression in the tumors, affecting relevant cellular processes. Similar cellular functions were found affected in BRCA1 not expressing andBRCA1 or2 mutated tumors. Hierarchical clustering classified hereditary breast tumors in four major, groups according to the type and amount of genomic alterations, showing one group with a significantly poor overall survival (p = 0.0221). Within this cluster, deletion ofPLEKHO1, GDF11, DARC, DAG1 andCD63 may be associated to the worse outcome of the patients. Conclusions These results support the fact that BRCA1 lack of expression in tumors should be used as a marker for BRCAness and to select these patients for synthetic lethality approaches such as treatment with PARP inhibitors. In addition, the identification of specific alterations in breast tumors associated with poor survival, immune response or with a BRCAness phenotype will allow the use of a more personalized treatment in these patients.